The discursive brand analysis of the accommodation units from the touristic basin of Suceviţa (Bukovina Region, Romania) - Codrin Dinu Vasiliu; Ion Sebastian Brumă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
In the rural areas where there is an economic potential clearly defined by the agricultural or commercial activities, tourism is the business key within reach. Under the circumstances, the socio-economic reflex takes the form of developing projects for tourist services, especially in the places with tourist potential. Further, the local economy, at least with respect to the private initiative, advances towards agritourism. In the present study we aim to run a discursive analysis of the presentation messages offered by 54 accommodation units from the touristic basin of Sucevi÷ta. Making an inventory of the online messages (own sites and platforms for touristic services) we could identify 24 key concepts (keywords and key phrases) and starting from their occurrences within the identity narratives of the accommodation units we have analysed their relationship with the supra themes and the themes belonging to the local and regional brand. Further on, we have outlined the general profile of the accommodation units and the profile of the target group as they appear in their presentation discourses. The relationship between these two profiles reveals strong brand connections but also shows some fractions which can be mended. To repair these inconsistencies, we provide a few handy recommendations in formulating medium and long-term strategies of development in the rural tourism.
Keywords: Z32; Z13; M31; O18; 330; discursive analysis; rural touristic unit; brand; Sucevi÷ta; Bukovina